Influence Use of Learning Media Interactive (Presentation Interactive Quizizz) in Increase Understanding the Theory of Hindu-Buddhist Entry into Indonesia among Students Class X.6 of SMA Negeri 2 Medan - Rosa, Elvina; Nugraha, Muhammad Adika; Aisyah, Sitti (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The use of interactive learning media has become the main focus of researchers in efforts to increase students' understanding of historical material regarding the theory of Hindu-Buddhist entry into Indonesia.This research aims to explore the influence of interactive learning media,especially the interactive presentation Quizizz,in increasing class X.6 students' understanding of this theory.The research method used is Classroom Action Research (PTK),with a focus on practical steps to improve learning in the classroom.The research results showed that through three action cycles,students' activity in learning increased significantly,along with increasing their understanding of the material.The final test results show a continuous increase in student achievement scores in each cycle.In conclusion,the implementation of interactive learning media,such as Quizizz interactive presentations,can help improve students' understanding of historical material,with learning activities that are more dynamic and student-oriented .